2006
DOI: 10.2474/trol.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carboxylic Acids on Friction and Wear Reducing Properties for Alkylmethylimidazolium Derived Ionic liquids

Abstract: Lubricant additive technology to improve lubricant performances is an important issue for ionic liquids to be applied practically. Effects of carboxylic acids with different carbon chain length in ionic liquid on tribological properties were examined. Solubility of carboxylic acids was dependent on the chain length of carboxylic acids and imidazolium cations. The carboxylic acids reduced friction and wear in comparison with additive free one. It was found that friction reducing properties of carboxylic acid de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 6 publications
4
30
0
Order By: Relevance
“…1. As we have reported previously, the pendulum friction test indicated that the friction coefficient of 1-alkyl-3-methylimidazolium salts decreased with an increase in the chain length of the alkyl group [12,14]. On the other hand, as shown in Fig.…”
Section: Determination Of Friction Coefficient Using Pendulum Frictiosupporting
confidence: 47%
See 1 more Smart Citation
“…1. As we have reported previously, the pendulum friction test indicated that the friction coefficient of 1-alkyl-3-methylimidazolium salts decreased with an increase in the chain length of the alkyl group [12,14]. On the other hand, as shown in Fig.…”
Section: Determination Of Friction Coefficient Using Pendulum Frictiosupporting
confidence: 47%
“…Higher alkyl groups in imidazolium cations are instrumental in improving the tribological properties of a compound. Further, hydrophobic anions afford a superior thermo-oxidative stability to RT-ILs as compared to hydrophilic ones [12,14]. The thermo-oxidative stability of RT-ILs decreases with increase in the chain length of the alkyl group in an imidazolium cation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc dialkyldithiophosphate (ZDDP) is a well-known lubricant additive and exhibites good tribological properties [18][19][20][21][22]. Fluorine-based ionic liquids exhibit superior tribological properties than ZDDP, because of the formation of tribo-films composed of FeF 2 and FeF 3 during sliding [8][9][10][11][12][13][14][15][16][17]23]. However, use of fluorine-based ionic liquids as a lubricant results in corrosion of metallic materials due to the formation of hydrogen fluoride [8,24].…”
Section: Introductionmentioning
confidence: 99%
“…They have been used as novel highperformance lubricants, because of their attractive properties, such as low vapor pressure, low volatility, high thermal stability, and high oxidation stability [4][5][6][7]. Most of the studies on ionic liquids as lubricants focus on fluorine-based ionic liquids, such as tetrafluoroborate, hexafluorophosphate, trifluoromethanesulfonate, and tris(perfluoroalkyl) trifluorophosphate [8][9][10][11][12][13][14][15][16][17]. Zinc dialkyldithiophosphate (ZDDP) is a well-known lubricant additive and exhibites good tribological properties [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Simple carboxylic acids improved the tribological properties of dialkylimidazorium-derived ionic liquids. 4 However, these carboxylic acids are volatile and corrosive. Based on our concept of molecular design of lubricant additives, 5 chemical modification of carboxylic acid by introduction of certain functional group was examined.…”
mentioning
confidence: 99%